Core–shell structured multiwall carbon nanotube–graphene oxide nanoribbon and its N-doped variant as anodes for high-power microbial fuel cells. Issue 10 (8th September 2020) - Liu, Yu-Chen; Hung, Yu-Hsuan; Liu, Shih-Fu; Guo, Chun-Han; Liu, Tzu-Yin; Sun, Chia-Liang; Chen, Han-Yi
Abstract : The MFCs with N-MWCNT@GONR and MWCNT@GONR anodes exhibits high power densities up to 3444 mW m −2 and 3291 mW m −2 . Abstract : A novel core–shell structured multiwall carbon nanotube–graphene oxide nanoribbon (MWCNT@GONR) and a nitrogen-doped MWCNT@GONR (N-MWCNT@GONR) were synthesized through a microwave energy-assisted unzipping process and utilized as anodes for Escherichia coli -based microbial fuel cells (MFCs) for the first time. To evaluate the electrochemical performance of the MFCs, we measured the electrochemical activity and charge transfer in MFCs with MWCNT, N-MWCNT@GONR, and MWCNT@GONR anodes. Compared to the MFC with the MWCNT anode (970 mW m −2 ), the MFCs with the N-MWCNT@GONR and MWCNT@GONR anodes exhibit higher power densities of up to 3444 and 3291 mW m −2, respectively. Both the oxygen and nitrogen functional groups on the MWCNT@GONR and N-MWCNT@GONR contribute to good biocompatibility, which greatly enhances the charge transfer efficiency and biofilm formation on the anode surface. Our results suggest that MWCNT@GONR and N-MWCNT@GONR are outstanding and promising anode materials for MFCs.